Unsafe Abortion: an Inequity in Health Care, Thailand Perspective - Chaturachinda, Kamheang; Boonthai, Nongluk (Journal of Population and Social Studies [JPSS], 2017)
“Women are not dying of diseases we cannot treat, they are dying because societies have yet to make the decision that their lives are worth saving” (Fathalla, 2006). “The underlying cause of morbidity and mortality from unsafe abortion today are not blood loss and infection but rather apathy and disdain toward women” (Grimes et al., 2006). Each year worldwide up to 68,000 women die due to unsafe abortion. Many thousands more are maimed for life from complications of unsafe abortion. In Thailand, up to 10-15 percent of maternal deaths are due to unsafe abortion. Many thousands of women are still hospitalized because of this preventable pandemic. The National Health Security Office had spent 150 million Baht of the annual health care budget on treating complications arising from unsafe abortion. Unsafe abortion is the termination of unintended or unwanted pregnancy by an unskilled individual without the necessary skill or conducted in a place that does not meet minimum medical standards. Among the factors that can lead to unsafe abortion are socio-economic, politic, religion and belief, legal, health care system, health care provider, and technology. The main barrier to the access of safe abortion service in Thailand is the negative attitude towards abortion on the part of health care providers. To rectify this there has to be a paradigm change in society and among health care providers.